2022
DOI: 10.1002/ange.202211792
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Enhanced Accessibility and Reproducibility of Worm‐like Micelles by In Situ Crosslinking Polymerization‐Induced Self‐Assembly

Abstract: Worm-like micelles have attracted great interest due to their anisotropic structures. However, the experimental conditions for obtaining worm-like micelles are very restricted, which usually causes seriously poor reproducibility. In this work, significantly enhanced accessibility of worm-like micelles is realized by in situ crosslinking polymerization-induced self-assembly (PISA). The reproducibility of worm-like micelles is greatly improved due to the significantly enlarged experimental windows of worm-like m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…44 The diameters of these micelles closely aligned with the theoretical value of 12.6 nm, supporting the proposed self-assembly mechanism (Figure S6). Such microstructures have been reported 45 to exhibit excellent capability in drug delivery to cells, as the worm-like structure enhances the probability that the particle can pass through the cell membrane. Additionally, worm-like micelles exhibit extended circulation time in the bloodstream, with micelle disassembly into smaller spherical particles resulting in faster clearance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…44 The diameters of these micelles closely aligned with the theoretical value of 12.6 nm, supporting the proposed self-assembly mechanism (Figure S6). Such microstructures have been reported 45 to exhibit excellent capability in drug delivery to cells, as the worm-like structure enhances the probability that the particle can pass through the cell membrane. Additionally, worm-like micelles exhibit extended circulation time in the bloodstream, with micelle disassembly into smaller spherical particles resulting in faster clearance.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been widely reported that the polymer concentration has an important influence on the morphology evolution in the PISA process. ,, Higher concentration results in a higher frequency of inelastic collision between the nano-objects, which facilitates the morphology evolution. In consideration of this aspect, RAFT dispersion copolymerization of MAEAC and MAEB targeted to PEG 45 - b -P­(MAEAC 0.6 - co -MAEB 0.4 ) 150 block copolymers with identical compositions was carried out at different polymer concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Polymerization-induced self-assembly (PISA), which effectively simplifies the procedure of producing polymeric nano-objects and allows preparing polymeric nano-objects in concentrated solution, has been demonstrated to be a powerful strategy. Recently, fabrication of polymeric nanotubes by PISA in a highly efficient manner has been reported by several groups. For example, O’Reilly and co-workers reported the preparation of polymeric nanotubes by polymerization-induced one-dimensional (1D) fusion of spherical vesicles in an aqueous ring-opening metathesis PISA formulation . The formation of nanotubes was attributed to the high glass-transition temperature ( T g ) and the rigid backbone of the poly­(norbornene) core-forming blocks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations